Molecular Dynamics Simulations of Normal Saline Solution associated with Microwave Frequencies - Zhen, Chen; Huang, Ka-Ma; Yang, Li-Jun (Asian Journal of Chemistry, 2010)
A series of molecular dynamics simulations of normal saline solutions at different electrical field frequencies, ranging from 1.00-2.45 GHz are performed, to investigate the effects of electrical field on the water molecule and ions in the normal saline solutions. The simple point charge model is used for water and the ions are modeled as charged Lennard-Jones particles. The local structure of the solution is investigated by computing the radial distribution functions of water-water, ion-water and ion-ion. The single-particle dynamics is investigated by calculating the self-diffusion coefficients of ions and water molecules. It is found that the probability of contact ion pair formation decreases and the probability of solvent separated ion pair formation increases, the randomization of position and orientation of water molecules increases and the water network become weak with the increasing frequency. Also, the translation movement of water molecule and ions increase and these movements have not linear relations with the frequency.